Penerapan Metode Fibonacci Code Dalam Mengkompresi File Video - Rizqina Silaban (STMIK Budi Darma, 2022)
In the current era of technological development, the need for large data storage capacity seems to be increasingly important. Therefore, despite the tremendous advances in data storage technology compression technique is no longer a stranger. because the data that must be stored the longer it will be more and more one of them is video file storage. This problem often arises because the large size of the data causes wasteful storage media used. To overcome the problem of size in storing data and the transmission process, the researchers will use the Fibonacci code algorithm to perform the compression process. The Fibonacci Code algorithm is one type of lossless data compression used in this study, whose performance will be measured by comparison parameters Compression Ratio (CR) and Redundancy (RD). The compression process is only performed on video files with the .mp4 format. The experimental results show that this algorithm is very effective, and can produce comparisons of Compression Ratio (CR) 51%, Ratio Of Compression (RC) 1.96% and Redundancy 49%. After getting the results of the video file compression, it will be designed into the Microsoft Visual Basic 2008 application